Assessment of Geoid Models Offshore Western Australia - Deng, Xiaoli; Coleman, R.; Featherstone, Will; Ridgway, K. (Coastal Education and Research Foundation, 2009)
In Western Australia, coastal dynamics are influenced by a major ocean boundary current system, the Leeuwin Current, which is characterised by mesoscale features. To fully under-stand the Leeuwin Current using satellite altimeter measurements, a precise (1-2 cm) and full-spatial-scale (<100 km) geoid model is crucial. This paper focuses on a comparison between two mean dynamic ocean topography models derived from independent hydro-graphic climatologies, and an altimeter-observed mean sea surface referenced to recently released geoid models offshore of Western Australia (20°S to 45°S, 108°E to 130°E). The geoid models used include combined global geopotential models from the GRACE satellite mission and AUSGeoid98. The estimated mean dynamic ocean topography models are compared to independent dynamic ocean topography from CSIRO's Atlas of Regional Seas (CARS) climatology. The results show that the EIGEN_GL04C and GGM02C+EGM96 global geopotential models to degree and order 360 give the best comparisons against CARS in the Leeuwin Current region, suggesting that they should be used in the future for computing the ocean transport, surface current velocities and dynamic topography, and be used as a reference field for future computations of regional marine geoid models.